Bespoke music - Narration for mental healthusing progressive muscle relaxation in Covid-19times / Valerie Ross ... [et al.] - Ross, Valerie; Amir, Abid (Universiti Teknologi MARA Cawangan Sarawak, 2020)
The COVID-19 pandemic has changed the global landscape of life leaving indelible vicissitudes wherever it strikes. The World Health Organisation reported over 48 million cases of infections and 1.2 million deaths in less than eight months since the outbreak was declared a pandemic in March 2020. Repeated national and regional lockdowns, job losses, isolation, marginalisation, deteriorating health conditions and a sense of uncertainty and helplessness among wide facets of societies have exerted unprecedented economic and psychosocial damage. Its toll on mental health is recognised as one of the major challenges affecting global communities. Innovative healthcare services are much needed. This study aimed to promote mental health by creating and using electroaccoustic music and pulse-based narration of instructional scripts premised on muscle relaxation techniques. An interdisciplinary practice-based methodology was adopted whereby a novel conceptual framework was designed and applied. The outcome of the study was the creation of Bespoke Music and Narration for Mental Health available both in the English Language and Malay Language. Positive feedback was reported from an experiential session by twenty-nine healthcare workers to gauge the clarity of the instructions and the effectiveness of the music with pulse-based narration in promoting relaxation.